Innovating Emancipated Curriculum Differentiation Learning Materials for X Grade Senior High School Students - Wijaya, Kadek Krisna; Netiasih, Putu Kerti; Mahayanti, Ni Wayan Surya (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This research aims to develop and analysis the quality of developing learning materials based on Emancipated Curriculum for 10th grade senior high school. The concept of the Emancipated Curriculum emerged based on provide freedom of thought, ensuring that students can independently access knowledge in formal and non-formal education without any restrictions.This research design will consist of four stages such as 1) Analysis, 2) Design, 3) Development, and 4) evaluation. Based on few expert, it can be called as ADDE models (W. & Creswell, 2010). The focus of D&D research includes analysis, planning, production, and evaluation. D&D research is also known as a method for creating procedures, techniques, and tools based on systematic analysis of specific situations. Various methods were used to collect data as follows observation sheet, interview, questionnaire and documetation. Analysis method that used in this research is using a mixed methods approach that includes both qualitative and quantitative based on the method questionnaire. The qualitative data will be obtained through interviews and observations with EFL teachers and students, with a particular focus on the syllabus and lesson plans. Quantitative data collected through questionnaires, on the other hand. The findings of the research are the learning needs required by students at schools A and B generally include several needs for visual, aural, kinesthetic, read and write learning styles. Differentiated learning materials are developed based on a blueprint that includes learning topics and subtopics, basic competencies, teaching methods, types of assessment, teacher guidelines, learning activities. Learning materials are designed to guide teachers in carrying out daily learning to achieve a learning objective. The product as a whole has been adapted to the independent curriculum, as it focuses on innovative teaching methods, and is also suitable for use in all situations as it focuses on 21st century skills. Even so, the material prepared still has several improvements, such as design revisions related to a more systematic layout. The material prepared in this research has also provided several clear instructions to support students' active learning starting from observation, observation and several related projects.